‘Triple P’ to Improve English Speaking Ability of Students in English Language and Literature Study Program Sawerigading University - Nazaruddin, Rezkiawati; Syamsuddin, Syamsuddin (Eduvelop: Journal of English Education and Development, 2018)
The purpose of this study is to find out whether the triple P model can Improve the students’ speaking skills. This research is a Classroom Action Research which applied to the students of English Language and Literature Study Program of Sawerigading University the academic year of 2016/2017. During the learning process, students are taught using â€˜Triple Pâ€™ model. This model includes three activities; presentation, practice and production. In general it can be concluded that this model could motivate the students to speak confidently in the classroom and showed the improvement of studentsâ€™ creativity on teaching learning process, their ability to express their own ideas, and their ability to interact or communicate with their friends.